Complications and predictors of diagnostic yield of endobronchial forceps biopsy in visible lesions - Shrestha, Bishow Kumar; Adhikari, Shital; Thakur, Binay Kumar; Kadaria, Dipen; Tamrakar, Kishore Kumar; Devkota, Mukti (Journal of Advances in Internal Medicine, 2019)
Background: Fiberoptic bronchoscopy is an important and relatively safe procedure for evaluation of various pulmonary diseases. Endobronchial forceps biopsy is commonly performed sampling technique for visible lesions in tracheobronchial tree. Diagnostic yield of biopsy depends upon lesion type and the number of biopsy samples taken. This study aimed to evaluate the complications and diagnostic yield of endobronchial forceps biopsy in visible lesions and correlate the number of biopsy samples taken with the yield.Methods: This was an observational study conducted at two tertiary care hospitals in Chitwan; Chitwan Medical College Teaching Hospital and B P Koirala Memorial Cancer Hospital. One hundred and forty patients who underwent endobronchial forceps biopsy of bronchoscopically visible lesions were included. Complications and diagnostic yield of the biopsy samples and its correlation with number of biopsies taken were evaluated.Results: The common complications observed were transient drop in saturation > 4% (22%) and mild bleeding (9.9%). The net diagnostic yield was 67.4% that significantly improved with an increase in the number of biopsies taken. The yield was better for exophytic growths compared to submucosal/ mucosal lesions (83.7% vs. 57%, OR = 8.1 (2.2 – 29.9), P